Case report: Scapulohumeral arthrodesis in a reindeer - Hankins, Kimery L.; Reed, Shannon K.; Ida, Keila K.; Watkins, Jeffrey P.; White, Sarah A. (Frontiers in Veterinary Science, 2023)
This case report describes the anesthetic, surgical, and postoperative management of scapulohumeral arthrodesis in a juvenile reindeer with severe lameness due to a chronic proximal humeral fracture and scapulohumeral luxation. The reindeer was managed with prolonged stall confinement and physical therapy and nine months postoperatively was walking and bearing weight equally when standing. This case demonstrates that comparative techniques from other veterinary species coupled with considerations for reindeer anesthesia can be successful in restoring functional soundness after scapulohumeral arthrodesis. Background Relatively few reports of scapulohumeral arthrodesis exist in large animals, in part due to the technicality of the procedure, lack of implant strength, and significant biomechanical forces on the joint. Severe osteoarthritis and traumatic luxation or subluxation of the joint are the most common reasons for the procedure. Although the overall use of scapulohumeral arthrodesis in large animals is not truly known, it is infrequent (2, 5). Scapulohumeral joint instability in large animals can be difficult to diagnose because of significant musculature within this region. Definitive diagnosis is usually achieved through radiographs or computed tomography. Described stabilization techniques in large animals include closed reduction with or without arthroscopy of the joint, open reduction and internal fixation with tension wires, or arthrodesis of the scapulohumeral joint; also recently, a glenoid ostectomy was successfully described in a miniature donkey (1,8,10,15). Complications or failure of reduction techniques are common. Scapulohumeral arthrodesis is often considered a salvage procedure and usually reserved for smaller equids. In small animal practice, scapulohumeral luxation is a common orthopedic problem especially in small canine breeds (10), and there are numerous reports of successful surgical management in dogs (10). There are also reports of such surgery performed on domestic hoofstock such as miniature and small horses, donkeys, and a variety